The correlation between blood glucose control obesity and diabetic duration, with frequency of dermatophytosis among type II diabetic patients. - Dwi Retno AW, Dwi Retno AW (Universitas Gadjah Mada, 2002)
Objectives: The aim of this study was to determine the correlation of blood glucose control and frequency of dermatophytosis among type II diabetic patients. In addition we also assessed the dermatophytosis in correlation with obesity and diabetic duration.Materials and Methods: The study was performed using a cross-sectional study design. The subjects of this study were 180 type II diabetic patients, divided into two groups of blood glucose level (good and poor glycemic control groups). In addition, these subjects were examined for evidence of dermatophytosis, and compared between good glycemic control and poor glycemic control. Among the subjects suspected to have dermatophytosis lesions were further examined using potassium hydroxide and fungal cultures.Results: The result showed that there was seemed to be an increased frequency of dermatophytosis in poor glycemic control group in comparison with the good glycemic control group (8.3% vs 6.1 %). Statistically this difference was significant (p0.05). The combination of glycemic control and obesity in this study was seemed to have a significant correlation too.Conclusion: poor glycemic control and or obesity increased the risk for suffering from dermatophytosis in the type II diabetics, while the diabetic duration did not increase.Keywords: dermatophytosis - type II diabetes - glycemic control - obesity - diabetic duration